The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s11095-013-1097-1
|View full text |Cite
|
Sign up to set email alerts
|

Drug Delivery Using Platelet Cancer Cell Interaction

Abstract: The proposed drug delivery strategy may lead to clinical improvement in the management of cancer treatment as lower drug concentration can be used in a targeted mode. Additionally the method can be personalized as patient's own platelet can be used for deliver various drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 26 publications
2
63
0
Order By: Relevance
“…The ascetic fluid is the direct nutritional source for carcinoma development because it meets the nutritional requirements of carcinoma cells. In a cytological study, Ehrlich cells showed induced mitotic cells and cellular changes and a rapid increase ascetic fluid volume in EAC untreated group according to Funasaka et al, Osman et al, and Sarkar et al who reported that the aggregation of ascetic fluid in the peritoneal cavity was either due to a decreased lymphatic recovery system which is linked with the crippling of the lymphatic by carcinoma cells, or because angiogenesis which detected in ascites tumor‐bearing peritoneal wall, or either due to microvessels hyperpermeability of the peritoneal cavity.…”
Section: Discussionmentioning
confidence: 95%
“…The ascetic fluid is the direct nutritional source for carcinoma development because it meets the nutritional requirements of carcinoma cells. In a cytological study, Ehrlich cells showed induced mitotic cells and cellular changes and a rapid increase ascetic fluid volume in EAC untreated group according to Funasaka et al, Osman et al, and Sarkar et al who reported that the aggregation of ascetic fluid in the peritoneal cavity was either due to a decreased lymphatic recovery system which is linked with the crippling of the lymphatic by carcinoma cells, or because angiogenesis which detected in ascites tumor‐bearing peritoneal wall, or either due to microvessels hyperpermeability of the peritoneal cavity.…”
Section: Discussionmentioning
confidence: 95%
“…). This should, however, not prevent us making a good use of the close engagements of platelets with cancer cells, to develop platelet‐targeted anti‐cancer agents and to utilize platelets as a carrier of anti‐cancer agents, which have been proposed and investigated before . For example, utilizing the properties of cancer cell‐induced platelet activation and high co‐localization rate of platelets at the invasive front of cancer and/or with metastatic niches/foci of cancer cells, development of activated platelet‐targeting carrier of anti‐cancer drugs will be an attractive approach for the guided anti‐cancer therapies.…”
Section: Research Perspectivesmentioning
confidence: 99%
“…Despite the key role of PLTs in the maintenance of hemostasis, they were shown to regulate multiple processes such as angiogenesis, cell differentiation, cell migration, immune responses and tissue remodeling (25)(26)(27). More recently, those PLT unique features have been exploited in the development of novel therapies such as in supporting wound healing, tissue regeneration or as drug carriers (28)(29)(30)(31). Due to the population aging, a significant increase on PLT demand for all those therapeutic approaches is expected.…”
Section: Hla-universal Mks Generate Plts In a Refractoriness Mouse Modelmentioning
confidence: 99%